A Study of the Differences in the Gas Diffusion and Migration Characteristics of Soft and Hard Coal in High Gas Coal Seams - Anying Yuan (Advances in Civil Engineering)
At the present time, it is of major significance to examine the differences in the gas diffusion and migration characteristics of soft and hard coal in order to prevent and control safety hazards in high gas coal seams. In this study, the differences in the gas diffusion and migration characteristics between soft coal and hard coal were examined in detail using macrostructural, mesostructural, and microstructural research methods. The root causes of the differences in the gas diffusion and migration between soft coal and hard coal were revealed in the obtained research results. The study shows that, in terms of the macrostructures, the soft coal particle grains were flakey and with shapes resembling fingernails. Meanwhile, the hard coal particle grains were observed to be in the shapes of complete blocks. In addition, in terms of the mesostructures of the different coal types, it was found that the proportion of granular coal below the particle size limit of 6 mm in the soft coal was much higher than that of the hard coal. Also, from the aspect of the characteristics of the microstructures, the pores and fissures on the soft coal surfaces were observed to be better developed, and the BJH specific surface areas of the soft coal were more than twice those of the hard coal. That is to say, the gas diffusion and migration conditions of the soft coal were better than those of the hard coal. At the same time, the increments of the specific surface areas and volumes of the pores of soft coal were above 100 nm, which provided channels for gas diffusion and migration at rates of more than twice those of the hard coal. Therefore, the soft coal was more conducive to gas emissions. This study conducted gas desorption experiments on both soft and hard coal samples and found that the initial gas desorption speed of the soft coal was significantly higher than that of the hard coal. Since the instantaneous gas emissions of the soft coal were significantly higher than those of the hard coal, it was considered to be more likely that gas outbursts and transfinite accidents could potentially occur in the soft coal layers of a project site. This study’s results provided a foundation and basis for effective gas control measures in coal seams composed of soft coal layers, which will be of major significance to the safety of coal mining activities in the future.